Determinants of Nurses’ Safety Attitudes in a Hospital Setting - Frima Ulfa Agustina; Hanny Handiyani; Tuti Afriani (Fakultas Ilmu Keperawatan Universitas Indonesia, 2022)
Hospital patient safety socialization is a routine part of nursing care. Although nurses’ knowledge of patient safety affects nurses’ safety attitudes, such knowledge may not be optimal. This study explored potential factors determining nurses’ safety attitudes in a hospital setting. This was a quantitative study with a cross-sectional design. The study population comprised 376 nurses who were recruited using the purposive sampling method. The instruments were valid and reliable. The test results were as follows: job satisfaction: 0.356–0.575 (Cronbach’s alpha: 0.724); workload: 0.338–0.613 (Cronbach alpha: 0.736), job stress: 0.542–0.719 (Cronbach’s alpha: 0.756); head nurse’s management function: 0.401–0.822 (Cronbach’s alpha: 0.760); working conditions: 0.488–0.670 (Cronbach’s alpha: 0.767); and nurses’ safety attitudes: 0.300–0.827 (Cronbach’s alpha: 0.771). The data were analyzed by bivariate and multivariate analyses, using structural equation modeling (SEM). The results revealed a relationship between the following variables and nurses’ safety attitudes: age (p = 0.001), work experience (p = 0.001), job satisfaction (p = 0.001), gender (p = 0.025), clinical nurses’ career path (p = 0.001), patient safety training (p = 0.032), workload (p = 0.001), work stress (p = 0.009), head nurse’s management function (p = 0.001), and working conditions (p = 0.001). Workload was the most influential factor affecting nurses’ safety attitudes (original sample = -0.776). To improve nurses’ safety attitudes, hospitals need to pay attention to nurses’ job satisfaction, workload, work stress, and working conditions and optimize the head nurse’s management function to improve nurses’ safety attitudes. Keywords: determinant, nurses, safety attitudes, workload Abstrak Determinan Sikap Keselamatan Perawat di Rumah Sakit. Sosialisasi keselamatan pasien rumah sakit telah rutin dilakukan, tetapi pengetahuan perawat tentang keselamatan pasien yang akan memengaruhi sikap keselamatan perawat masih belum optimal. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi (determinan) sikap keselamatan perawat di rumah sakit. Penelitian kuantitatif dengan desain cross sectional ini dilakukan pada 376 perawat yang diambil dengan metode purposive sampling. Instrumen tersebut valid dan reliabel dengan hasil uji kepuasan kerja adalah 0,356–0,575 (Cronbach alpha’s 0,724), beban kerja adalah 0,338–0,613 (Cronbach alpha’s 0,736), stres kerja adalah 0,542–0,719 (Cronbach alpha’s 0,756), fungsi manajemen kepala ruangan adalah 0,401–0,822 (Cronbach alpha’s 0,760), kondisi kerja adalah 0,488–0,670 (Cronbach alpha’s 0,767), sikap keselamatan adalah 0,300–0,827 (Cronbach alpha’s 0,771). Data dianalisis secara bivariat dan multivariat dengan menggunakan Structural Equation Model. Ada hubungan antara umur (p = 0,001), pengalaman kerja (p = 0,001), kepuasan kerja (p = 0,001), jenis kelamin (p = 0,025), jenjang karir perawat klinik (p = 0,001), pelatihan keselamatan pasien (p = 0,032), beban kerja (p = 0,001), stres kerja (p = 0,009), fungsi manajemen kepala perawat (p = 0,001), dan kondisi kerja (p = 0,001) dengan sikap keselamatan perawat. Faktor yang paling berpengaruh terhadap sikap keselamatan perawat adalah beban kerja (Original sample = -0,776). Rumah sakit perlu memperhatikan kepuasan kerja perawat, beban kerja, stres kerja, kondisi kerja, dan optimalisasi fungsi manajemen kepala perawat untuk meningkatkan sikap keselamatan perawat. Kata Kunci: beban kerja, determinan, perawat, sikap keselamatan